2015
DOI: 10.1186/s13054-015-0736-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose dexamethasone on perioperative lactate levels and glucose control: a randomized controlled trial

Abstract: IntroductionBlood lactate levels are increasingly used to monitor patients. Steroids are frequently administered to critically ill patients. However, the effect of steroids on lactate levels has not been adequately investigated. We studied the effect of a single intraoperative high dose of dexamethasone on lactate and glucose levels in patients undergoing cardiac surgery.MethodsThe Dexamethasone for Cardiac Surgery (DECS) trial was a multicenter randomized trial on the effect of dexamethasone 1 mg/kg versus pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 31 publications
2
36
1
2
Order By: Relevance
“…These results were similar to an earlier study, also showing an increase in blood lactate concentrations in healthy dogs after administration of methylprednisolone . This phenomenon also is observed in human medicine, where cardiac surgery patients receiving a single perioperative high dose of dexamethasone had increased blood lactate (2.1 mmol/L versus 0.7 mmol/L) and blood glucose concentrations (10.0 mmol/L versus 8.0 mmol/L) after surgery compared to the placebo group . Similarly, an increase in blood lactate concentrations also was observed in humans with Cushing's disease or after corticosteroid administration …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results were similar to an earlier study, also showing an increase in blood lactate concentrations in healthy dogs after administration of methylprednisolone . This phenomenon also is observed in human medicine, where cardiac surgery patients receiving a single perioperative high dose of dexamethasone had increased blood lactate (2.1 mmol/L versus 0.7 mmol/L) and blood glucose concentrations (10.0 mmol/L versus 8.0 mmol/L) after surgery compared to the placebo group . Similarly, an increase in blood lactate concentrations also was observed in humans with Cushing's disease or after corticosteroid administration …”
Section: Discussionsupporting
confidence: 89%
“…Dexamethasone is a corticosteroid often used in equine practice to treat a variety of diseases such as recurrent airway obstruction, inflammatory airway disease, or hemolytic anemia, with suggested dosages ranging from 0.05 to 0.1 mg/kg q24h . A previous study in dogs showed that administration of prednisone caused a statistically significant increase in lactate concentrations, a phenomenon also reported in humans . The mechanism behind this effect is not fully understood, but may be related to the effect of corticosteroids on carbohydrate metabolism, whereby increased rates of glucose production and utilization lead to increased production of pyruvate and lactate …”
mentioning
confidence: 99%
“…The doses of DEX from 0.035 to 1 mg/kg were widely prescribed in clinic for treating many diseases (Dieleman et al, 2011;Din et al, 2015;Ottens et al, 2015), while the doses from 0.5 to 80 mg/kg, especially 5 mg/kg, were widely used in animals to study the neurodegenerative diseases (Danilczuk et al, 2005(Danilczuk et al, , 2006Green et al, 2006). Our previous studies showed that chronic stress (8 weeks) and DEX (5 mg/kg) treatment for 21 days induced learning and memory impairment and hippocampal neurodegeneration (Li et al, 2010;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bazı gözlemsel yapılan çalışmalarda, hematokrit değerindeki düşüklük ile laktat seviyesinde yükselme olduğu gösterilmiştir [9,20,21] . Fakat randomize yapı-lan bir araştırmada, hematokrit değeri %20 ile %25 olan hasta grupları karşılaştırılmış, intraoperatif ve postoperatif dönemde laktat düzeyinde artma ile bir ilişkisi olmadığı sonucuna varılmıştır [22] .…”
Section: Komplikasyonlarunclassified
“…Oksijen sunumu kritik bir değerin altına düştüğünde oksijen tüketimi sunuma bağımlı hâle gelmekte ve laktik asidoz oluşmaktadır [5,6] . Kardiyopulmoner baypas sırasında inflamatuar yanıt olarak salınan bazı sitokinler ve diyabetojenik hormonlar laktat yüksekliğine, insülin rezistansına ve kan şekerinde artışa neden olmaktadır [7][8][9] . Yapı-lan çalışmalarda da ayrıca uzamış kardiyopulmoner baypasın yüksek laktat seviyeleri için bir risk faktörü olduğu belirtilmektedir [10][11][12] .…”
Section: Introductionunclassified